Evaluación de indicadores para lograr la certificación EDGE en la Urbanización La Joya, Etapa Quarzo - Vera Mera, Ricardo Alejandro (2024)
The study focuses on "EVALUATION OF INDICATORS TO ACHIEVE EDGE CERTIFICATION IN LA JOYA URBANIZATION, QUARZO STAGE", aiming to assess the necessary indicators for EDGE certification. It adopts a mixed approach, combining quantitative analysis of energy efficiency and water consumption with qualitative data on residents' and experts' perceptions. Surveys, observations, and interviews are used for data collection. Results reveal limited knowledge about EDGE but a strong community commitment to sustainability. Recommendations include improving infrastructure, expanding sustainability education, and increasing community participation to align La Joya with EDGE standards.